Anda di halaman 1dari 17

Integration

References: (1) Business Mathematics by Qazi Zameeruddin, V. K. Khanna and S.K. Bhambri (2) Schaum’s Outlines, Calculus by Frank Ayres, Jr. and Elliot Mendelson (4 th Edition)

Integration or antidifferentiation is the reverse process of differentiation. It is the process

of finding an original function when the derivative of the function is given.

1. Antiderivative and the Indefinite Integral (Ref 1: pg. 630-632, Ref 2: pg.

196-198)

Definition:

A function F(x) is called an antiderivative of the function f(x) if F (x) = f(x) for all x in

the domain of f(x).

Example:

(1)

(2)

If f(x) = 3x 2 then F(x) = x 3 is an antiderivative of f(x) since F (x) = 3x 2 = f(x). If f(x) = cos x then F(x) = sin x is an antiderivative of f(x) since F (x) = cos x = f(x).

(3)

If f(x) = x 4 then F(x) =

5

x

5

is an antiderivative of f(x) since F (x) = x 4 = f(x).

Example:

Consider the following functions and their derivatives.

(i)

(ii)

(iii)

(iv) If F 4 (x) = x 3 +

If F 1 (x) = x 3 , then

If F 2 (x) = x 3 + 5, then If F 3 (x) = x 3 - 10, then

Fx ) = 3x

1

(

2

Fx ) = 3x

2

(

Fx

(

Fx ) = 3x

2

) = 3x

3

4

(

2

= 3 x 2 ( F ′ x ( F ′ x ) = 3 x

2 , then

2

Therefore, if f(x) = 3x 2 , then F 1 (x) = x 3 , F 2 (x) = x 3 + 5, F 3 (x) = x 3 – 10 and F 4 (x) = x 3 + are all antiderivatives of f(x) = 3x 2 .

2
2

We see from the above example, that the antiderivative of a function is not unique. If F(x)

is

of f(x), since

an antiderivative of f(x), then F(x) + c (where c is a constant) is also an antiderivative

d

dx

[F (x)

+

c]

=

F (x)

.

Theorem:

If F 1 (x) and F 2 (x) are antiderivatives of a function f, then F 1 (x) - F 2 (x) = C, where C is a

constant.

It follows from the above theorem that if F 1 (x) is an antiderivative of a function f(x), then every other antiderivative of f(x) is given by F(x) = F 1 (x) + C, where C is an arbitrary constant. C is called the constant of integration.

We denote the process of integration by the symbol which is called an integral sign.

The expression

is also called the indefinite integral of f (x ). In this

notation, f(x) is called the integrand of the indefinite integral and the x in dx is the

variable of integration.

denotes any antiderivative of f(x); i.e., if = f(x) then

f (x)dx

+

C.

F (x)

f (x)dx

= F(x)

f (x)dx

f (x)dx

is read as ‘the integral of f(x) with respect to x’.

Since differentiation is the inverse operation of integration,

d

dx

[

f (x)dx] = f (x)

And since integration is the inverse operation of differentiation,

f (x)dx = f (x) + C .

Rules of Integration

(1)

kdx = kx + C

(k a constant)

(2)

(3)

kf (x)dx = k

f (x)dx

(k a constant)

g(x)dx

[ f (x) + g(x)]dx =

f (x)dx +

(4)

(5)

(

x

dx =

g x

(

))

r

r

r + 1

x

r

g

+ 1

(

+ C

,

x ) dx

=

( r ≠ −1 )

(

g

(

x

))

r

+ 1

r

+ 1

+ C

,

( r ≠ −1 )

[since

d

(

kx

+

C

) =

k

]

dx

d

x

r

+ 1

[since

(

 

+

C

)

=

x

 

dx

r

+ 1

 

r

]

r + 1 d ( g ( x )) r [since [ + C ]
r
+ 1
d
(
g
(
x
))
r
[since
[
+
C
]
=
(
g
(
x
))
g
(
x
) ]
dx
r + 1
Example:
(1)
3
dx =
3
x + C
by applying (1) above

(2)

(3)

6 6 x 2 x 5 ∫ 4 x dx = 4 + C =
6
6
x
2 x
5
∫ 4
x
dx =
4
+
C
=
+ C
6
3
3
1
x
2
[2
x
2
+
10]
dx =
2
+
10 x
+
3

2

by applying (2) and (4) above

C =

4 x

3

2

3

+

10 x

+

C

by applying (1), (2), (3) and

(4)

(4) above

4(4

x

+ 1)

2

dx

=

(4

x +

1)

3

3

+ C

by applying (5) above

2. Table of Indefinite Integrals (Ref 1: pg. 630-631, Ref 2: pg. 198, 225-228, 234 – 237)

1.

x

r

dx =

r

x

+ 1

+

C

(

r

≠− 1 )

since

 

d

(

r

x

+ 1

+

C

) =

r

x

r

+ 1

   

dx

r

+ 1

 

2.

1

dx = ln x
dx = ln
x

+

C

(

x

0

)

 

since

d

(ln x + C ) =
(ln
x
+
C )
=

1

 

x

g ′ ( x ) dx = ln g ( x )
g
′ (
x
)
dx = ln
g
(
x
)

g

(

x

)

+ C

 

dx

x

3.

a x dx =

a

x

ln a

+

C

(0

<

a

,

a

1)

since

d

dx

(

a

x

+

ln a

C

) =

a

x

4.

e

x

dx

=

e

x

+ C

 

since

d

(

e

x

+

C

) =

e

x

 

dx

5.

sin xdx = − cos x + C

 

since

d

(cos

x

+

C

) = sin

x

 

dx

6.

cos xdx = sin x + C

 

since

d

(sin

x

+

C

) = cos

x

 

dx

7.

sec

2

xdx =

tan x + C

 

since

d

(tan

x

+

C

) = sec

2

x

π

(x ≠ + kπ k = ± ±

2

,

0,

1,

2,

)

dx

8.

2

cos ec xdx = − cot x + C

 

since

d

(cot

x

+

C

) = cos

ec

2

x

 

dx

 

(x

kπ , k = 0,±1,±2,

)

9.

tan

xdx =−

ln

cos x
cos x

+ C

π

(x ≠ + kπ k = ± ±

2

,

0,

1,

2,

)

10.

cot

xdx

= ln

sin x
sin x

+ C

 

(x

kπ , k = 0,±1,±2,

 

)

 

 

11.

cos

ecxdx

= ln

cos

ecx

cot

x

+ C

12.

sec

xdx

= ln

sec

x +

tan

x

+ C

13.

dx

− − = sin + =− C cos 2 2 a a a − x
=
sin
+ =−
C
cos
2
2
a
a
a
x

1

x

1

x

+ C

(

x
x

< a

)

 

dx

1

1

1

x x

1

 

14.

 

+ C

 
 

=

tan

C

+ =−

cot

(a > 0)

 

2

2

   
 

a

+

x

 

a

a a

a

 
 

dx

 

1

1

x

15.

= sec 2 2 a a x x − a
=
sec
2
2
a
a
x
x
a

+ C

(x > a > 0)

 

3.

The Substitution Method (Ref 1: pg. 637-638, 640, Ref 2: pg. 198, 289-294)

f (g(x))g (x)dx =

f (u)du

where u is replaced by g(x) after the right-hand side is evaluated.

Justification:

Let u = g(x). Then

du =

dx

g (x)

.

d

dx

(

f

(

u du

)

d

(

du

) =

du

dx

f

du

(

u du

)

)

by applying the chain rule

= since differentiation is the reverse of integration

f (u).

dx

= f (g(x))g (x)

Therefore,

f (u)du =

f (g(x))g(x)dx

by the definition of the antiderivative.

Example:

(1) ∫ tan xdx = sin x ∫ cos x dx . Let u =
(1) ∫ tan xdx =
sin x
∫ cos x
dx
.
Let u = cos x. Then
du = − sin x
dx
sin x
1
Therefore,
dx =
∫ −
du
by substitution
cos x
u
1
du
=− ln
u
+ C
u
Therefore,
∫ tan xdx
= − ln
cos x
+ C
by substituting back u = cos x.

2

x (2) dx ∫ 2 3 x + 5 du = 1 du = 2
x
(2)
dx
∫ 2
3
x
+ 5
du =
1 du =
2
Let u = 2x 3 + 5. Then
6x
2 . Therefore,
x
dx
6 dx
2
x
1
1
1
1
3
Thus
dx
=
du =
ln
u
+
C
=
ln
2
x
+ 5
∫ 2
3
x
+ 5
6
u
6
6

(3) (cos x + 4) sin xdx

3

+ C

Let u = cos x + 4 . Then du = − sin x .
Let u = cos x + 4 .
Then
du = − sin x
.
dx
4
4
u
(cos
x +
4)
3
3
Therefore,
∫ (cos x + 4) sin xdx
=
u
du
=− + =−
C
4
4
1
(4) ∫
dx where a is a constant.
x − a
du
Let u = x – a. Then
= 1
.
dx
1
1
dx =
du
= ln
u
+
C
= ln
x − a
+ C
.
x − a
u

+ C

4. Integration by Parts (Ref 1: pg. 649-651, Ref 2: pg. 281-283)

(uv)dx = uv

(vu)dx

Justification:

(u(x)v(x))′ = u(x)v(x) + u(x)v(x)

Therefore,

(u(x)v(x))dx =

=

[u(x)v(x) + u(x)v(x)]dx

u

(

x ) v

u(x)v(x)dx

(

x ) dx

+

u

(

x ) v

(

v(x)u(x)dx

x

)

dx

i.e.,

Therefore,

u(x)v(x) =

v(x)u(x)dx +

u(x)v(x)dx = u(x)v(x)

Another way of writing this is:

udv = uv

vdu

Justification:

d

[

udv ] =

d

[

udv

].

dv

dx

dv

dx

by the chain rule.

Also,

d

udv = u

and hence

d

[

udv

]

dv

dv

dv

 

dx

Thus

d

[

udv ] =

d

[

udv

]

dv

=uv

 
   

.

 

dx

dv

dx

Hence

udv =

uvdx

.

= u v

.

.

Similarly

Therefore,

vdu =

vudx

uvdx = uv

vudx

may also be written as

udv = uv

vdu

This technique enables us to replace the ‘harder’ integration udv

integration vdu .

Example:

(1) xe

2x

dx

Let u = x and dv = e 2x dx.

Then du = dx

and v =

dv

=

e

2 x

dx

=

2 x

e

2

(2)

Therefore, by applying

udv = uv

vdu we obtain

 

2

x

2

x

2

x

2

x

xe

2x

dx =

x

e

e

dx

=

xe

e

+ C

 
       
 

2

 

2

 

2

4

 

ln xdx

 

Let u = ln x and let dv = dx.

 

Then

du

=

1

and v = x

 

dx

x

Therefore,

ln xdx

= xlnx -

x

.

1

dx = x

ln

x

dx = x

x

 

ln

x x + C

(3)

cos

3

xdx =

cos

2

x cos xdx

Let u = cos 2 x and dv = cos xdx

Then

du = −2 cos sin

dx

cos

x

and

cos

2

cos

cos

cos

2

2

2

dv =

cos xdx = sin x

x

v =

Therefore,

3

xdx =

=

=

=

x cos xdx

x sin x

x sin x + 2

2

x

sin x(2 cos x sin x)dx

cos x(1 cos

cos

xdx

2

2

x)dx

cos

3

xdx

sin

x +

Therefore,

3

cos

3

xdx = cos

2

x sin x + 2 cos xdx

Thus

cos 3

xdx =

1

2

cos

2

x

sin

x +

3

3

sin

x + C

.

Note: The integral

found by making the substitution u = sin x

3

xdx =

cos

cos

2

x cos xdx =

(1 sin

2

x) cos xdx

by an ‘easier’

may also be

5.

Partial Fractions (Ref 2: pg. 304-309)

A function of the form

N

(

x

)

D

(

x

)

where N(x) and D(x) are polynomials is called a rational

function. N(x) is the numerator and D(x) is the denominator. Suppose the degree of

N(x) is n and the degree of D(x) is m. If n < m, then

N

(

x

)

D

(

x

)

is said to be a proper fraction.

If n m ,

N

(

x

)

D

(

x

)

is called an improper fraction.

An improper fraction can be expressed as the sum of a polynomial and a proper fraction;

, we can divide the numerator by the denominator, obtaining as quotient a

polynomial Q(x) of degree n m, and as remainder a polynomial R(x) of degree not greater than m – 1.

for, if

n m

N

(

x

)

D

(

x

)

= Q(x) +

R

(

x

)

D

(

x

)

.

A polynomial is said to be irreducible, if it cannot be written as a product of two

f (x) = ax + b is automatically

irreducible.

polynomials of lower degree. Any linear polynomial

If we consider a quadratic

b

2

4

ac <

0

.

g

(

x

)

2

= ax

+ bx + c ,

this

is

irreducible if and only if

Theorem:

Any polynomial D(x) can be written as a product of linear factors and irreducible quadratic factors.

Partial Fractions

A

cx

+

d

rational function of the form (x

a)(x

and

b)

where a b may be expressed as the sum

B . These two fractions are called the

A

(x

a)

of two fractions of the form

(x

b)

partial fractions corresponding to the given rational function.

We determine the constants A and B as follows:

cx

+

d

   

A where a b .

B

Suppose (x

a)(x

− −

b)

=

(x

a)

+

(x

b)

Then (x

cx

+ d

A (

x

b

)

+

B

(

x

a

)

a)(x

b) =

 

(

x

a

)(

x

b

)

.

Therefore, cx + d = A(x b) + B(x a)

Substituting x = a we obtain

Substituting x = b we obtain

A

=

B =

ca

+

d

a

cb

+

b

d

b

a

.

cx

+

d

ca

+

d

cb

+

d

Therefore, (x

a)(x

b)

(

a

b

)(

x

a

)

(b

a)(x

b)

=

+

We may also obtain the constants by equating the coefficients on the left and right sides

of

cx + d = A(x b) + B(x a) .

x:

constant

c = A + B d = -bA aB

and solving these simultaneous equations for A and B

We give below by examples, the method of finding the partial fractions of rational functions that are proper fractions.

Case

 

I:

The

denominator

 

D(x)

 

is

a

product

 

of

distinct

 

(

x a

1

),(

x a

2

)

,(

x a

r

) .

 

Then

N

(

x

)

N

(

x

)

=

A

1

+

 

A

2

+

+

A

r

D

(

x

)

=

(

x

a

1

)(

x

a

2

)

(

x

a

r

)

(

x

a

1

)

(

x

a

2

)

(

x

a

r

)

 

2

x +

1

 

Example: (

x

1)(

x

2)(

x

3)

 
 

2

x +

1

 

A

 

B

 

C

 
   

+

+

 

Let (

x

1)(

x

2)(

x

3) = (

x

1)

(

x

2)

(

x

3)

.

 

2

x

+

1

 

(

A x

2)(

x

3)

+

B

(

x

1)(

x

3)

+

C

(

x

1)(

x

2)

Then (

x

1)(

x

2)(

x

3) =

 

(

x

1)(

x

2)(

x

3)

.

linear

factors

Therefore, 2x + 1 = A(x 2)(x 3) + B(x 1)(x 3) + C(x 1)(x 2) .

3

.

Substituting x = 2 we obtain 5 = B(1)(-1). Therefore, B = −5 .

Substituting x = 3 we obtain 7 = C(2)(1). Therefore,

Substituting x = 1 we obtain 3 = A(-1)(-2). Therefore,

A =

2

7

2

.

=

 

C =

 

3

5

7

 

+

2(

x

1)

(

x

2)

2(

x

3)

2

x

+

1

Thus (

x

1)(

x

− −

2)(

x

3)

Case II: The denominator D(x) = (x a) k

Then

N

(

x

)

A

1

+

A

2

+

+

A

k

D

(

x

)

=

(

x

a

)

(

x

a

) 2

(

x

a

)

k

.

x 1

Example:

(

x +

3)

3

 

x

1

A

B C

 

Let

 

=

+

 

3

+ 2

 

(

 

+ 3)

3

 

(

x +

3)

 

( x + 3)

(

x

+

3)

x

Then x 1 = A(x + 3) +

Substituting x = -3 we obtain -4 = C Equating the coefficient of x 2 we obtain 0 = A Equating the coefficient of x we obtain 1 = 6A + B. Since A = 0 we obtain B = 1.

2

B(x + 3) + C

Thus

x

1

 

=

 

1

 

4

(

x +

3)

3

(

x +

3)

2

(

x +

3)

3

 

Case

III:

 

The

 

denominator

 

D(x)

 

is

a

product

 

of

quadratics (

)

N

(

x

x

2

+ B x + C

1

P x

1

+

Q

1

1

), (

x

2

+ B

2

x + C

P x

2

+

Q

2

2

),

 

,

(

2

x

+ B

k

x + C

P x

k

+

k

) .

Q

k

Then

 

+

 

+

+

 

D

(

x

)

=

2

x

+

B x

1

+

C

1

 

2

x

+

B

2

x

+

C

2

x

2

+

B

k

x

+

C

k

Example: (

x

 

2

x

1

2

+

1)(

x

2

+

2)

 
 

2

x

1

Ax + B

Dx + E

 

Let

=

+

 
 

(

x

2

+

1)(

x

2

+

2)

 

2

x

+

1

x 2

+

2

.

Then 2

x

1

=

(

Ax + B

)(

2

x

+

2)

+

(

Dx + E

)(

x

2

+

1)

distinct

irreducible

Substituting x = 0 we obtain -1 = 2B + E ------------(i) Equating the coefficient of x 3 we obtain 0 = A + D. i.e., D = -A -----------------(ii) Equating the coefficient of x 2 we obtain 0 = B + E. Thus B = -E ---------------(iii) Substituting this into (i) we obtain E = 1 and hence B = -1 Equating the coefficient of x we obtain 2 = 2A + D. Substituting for D from (ii) we obtain A = 2 and therefore D = -2

 

2

x

1

2

x

1

2 x +

1

 

=

+

x

2

+

1)(

x

2

+

2)

x

2

+ 1

 

x 2 + 2

Thus (

Case IV: The denominator D(x) =

Then

N

(

x

)

P x

1

+

Q

1

P x

2

(x

2 +

+

Q

2

bx

+

c)

k

where

P x

k

+

2

x

Q

k

 
 

+

+

+

D

(

x

)

=

x

2

+

bx

+

c

(

x

2

+

bx

+

c

)

2

(

x

2

+

bx

+

c

)

k

+ bx + c

is irreducible.

 

3

Example:

 

x

(